The idea of the actor : drama and the ethics of performance - Worthen, William B., 1955- (Princeton University Press, 1984)
Analyzing the relationship between dramatic action and the controversial art of acting, William Worthen demonstrates that what it means to act, to be an actor, and to communicate through acting embodies both an ethics of acting and a poetics of drama. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.